Wattled Brushturkey hunting system in the Sigim and Sinaitousi communities in the buffer zone of the Arfak Mountain Nature Reserve, West Papua, Indonesia - HOTLAN MANIK; HUSMY YURMIATY; INDRAWATI YUDHA ASMARA; HANDARTO HANDARTO; JOHAN ISKANDAR; RUHYAT PARTASASMITA (Biodiversitas Journal of Biological Diversity, 2018)
Manik H, Yurmiaty H, Asmara IY, Handarto, Iskandar J, Partasasmita R. 2018. Wattled Brushturkey hunting system in the Sigim and Sinaitousi communities in the buffer zone of the Arfak Mountain Nature Reserve, West Papua, Indonesia. Biodiversitas 19: 849-856. Illegal hunting is still the cause of the decline of wildlife populations in nature. This is particularly the case with protected wildlife and endemic species, such as the Wattled Brushturkey in Palau West Papuan. Thus, research needs to be done on the hunting system at the site. The aim of this research was to know Wattled Brushturkey (Aepypodius arfakianus) hunting system by Sigim and Sinaitousi villagers, Arfak Mountains of West Papua. The research used descriptive method with field observation technique and semi-structured interviews. The results showed that the main purpose of hunting Wattled Brushturkey conducted by the Sigim and Sinaitousi communities is to consume the meat, while a part of egg hunting is for sale. The hunting by the two villagers was generally done in groups. The frequency of hunting depends on needs and demand. Hunting is done using snares, dogs, and combinations of snares and dogs. The tools used are snares, machetes, air rifles, arrows nad bows. The modern tools such as gun have been used in both villages. The hunting of Wattled Brushturkey begins in the morning and continues until late afternoon. The location of hunting is usually primary forest, secondary forest of former garden and river basin.